1999
DOI: 10.1152/ajpheart.1999.277.2.h848
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide activity in the peripheral vasculature during normotensive and preeclamptic pregnancy

Abstract: We investigated the role of nitric oxide (NO) in the vascular resistance changes of normotensive and preeclamptic pregnancy. Forearm blood flow (FBF) responses to brachial artery infusion of N G-monomethyl-l-arginine (l-NMMA), an NO synthase inhibitor, and angiotensin II (ANG II), an NO-independent vasoconstrictor, were determined by plethysmography in 20 nonpregnant women, 20 normotensive primigravidae, and 15 primigravidae with untreated preeclampsia. In pregnant subjects, FBF was reduced to nonpregnancy lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
56
2
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 41 publications
3
56
2
5
Order By: Relevance
“…Adequately diet-controlled studies of (nitrite+nitrate) excretion have yet to be performed in women with PE, although a study of plasma concentrations after one day of dietary control reported higher levels than in normotensive pregnant women. 174 Anumba et al (1999) 145 reported no difference in response to inhibition of NO synthase between normal and pre-eclamptic pregnant women. The surrogate measurement of cGMP will also reflect plasma concentrations of atrial natriuretic peptide, 175 which have also been reported to be higher in PE (eg, Thomsen et al, 1987 176 ; Irons et al, 1997 177 ).…”
Section: The Cardiovascular Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequately diet-controlled studies of (nitrite+nitrate) excretion have yet to be performed in women with PE, although a study of plasma concentrations after one day of dietary control reported higher levels than in normotensive pregnant women. 174 Anumba et al (1999) 145 reported no difference in response to inhibition of NO synthase between normal and pre-eclamptic pregnant women. The surrogate measurement of cGMP will also reflect plasma concentrations of atrial natriuretic peptide, 175 which have also been reported to be higher in PE (eg, Thomsen et al, 1987 176 ; Irons et al, 1997 177 ).…”
Section: The Cardiovascular Systemmentioning
confidence: 99%
“…148 Furthermore, forearm blood flow in women with GH or PE was either unchanged 144 or somewhat increased. 145,149 This suggests that the abnormalities of tone found in established disease represent homeostatic, rather than primary pathological, mechanisms. Women with severe PE have reduced venous distensibility antepartum, but are indistinguishable after delivery from women who were normotensive during pregnancy.…”
Section: The Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Impaired endothelium-dependent responses have been reported in systemic vessels isolated from women with PE. 3,4 Moreover, numerous studies have demonstrated disparities in terms of the relative contributions of nitric oxide (NO), endothelium-derived hyperpolarizing factor (EDHF), and prostacyclin (PGI 2 ) to vasodilatation in both physiological [5][6][7][8] and pathophysiological pregnancies. 3,6,9 In addition, the vascular dysfunction associated with PE has been shown to be induced by one or more circulating mediators as impaired relaxation was detected in resistance vessels exposed to plasma from women with PE.…”
mentioning
confidence: 99%
“…The physiological adaptations to pregnancy (increased blood volume, increased cardiac output, and sodium retention) are accompanied by an increase in nitric oxide (NO) biosynthesis (2,7,25). Because NO has been shown to suppress baroreceptor activity (18), we proposed that NO might also be responsible for blunting atrial volume receptor activity.…”
mentioning
confidence: 99%